2019
DOI: 10.1186/s12891-019-2517-0
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral ligament of the knee: a step-by-step dissection

Abstract: Background The number of studies and clinical interest in the anterolateral ligament of the knee (ALL) has grown in recent years. A meticulous and accurate ALL dissection is vital in anatomic and biomechanical studies, and a standardized technique is not yet established. As such, the aim of this study was to describe a step-by-step ALL dissection technique that could help authors consistently identify the ALL. Methods Twenty knees from frozen adult cadavers, with no pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Various cadaveric studies have demonstrated the presence of ALL in 50-100% of specimens [7][8][9][16][17][18][19]. In our study, ALL was present in 79% of the specimens (Figure 1, Figure 2, Figure 3).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Various cadaveric studies have demonstrated the presence of ALL in 50-100% of specimens [7][8][9][16][17][18][19]. In our study, ALL was present in 79% of the specimens (Figure 1, Figure 2, Figure 3).…”
Section: Discussionsupporting
confidence: 61%
“…Lateral extra-articular reinforcement procedures have been used since the 1970s as a possible solution for persistent ALRI after primary ACL reconstruction [3,6]. There has been a renewed worldwide interest in defining the anterolateral corner of the knee following the publication of the precise anatomic details of the anterolateral ligament (ALL) [7][8][9]. Cadaveric as well as clinical studies have reported on the benefits of supplementing ALL reconstruction with ACL reconstruction in cases with concomitant injuries [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…40,41,42 ALL was clearly demonstrated on 3.0T MRI and through step by step dissection method. 43,44 According to Claes et al origin of ALL is from the lateral femoral epicondyle, just anterior to the origin of lateral collateral ligament and passing caudally in close association with the body of the lateral meniscus to insert onto the proximal tibia between Gerdy tubercle and fibular head. 45 It is an anterolateral stabilizer of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…All cadavers were dissected by a single surgeon (D.S.) using techniques described in the literature [ 2 , 26 , 27 , 28 ]. Care was taken to prevent unnecessary excision of tissue.…”
Section: Methodsmentioning
confidence: 99%